2008
DOI: 10.1002/pmic.200700265
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the pathophysiological process involved in the antisnake venom effect of Mucuna pruriens extract

Abstract: Previously, we reported the antisnake venom properties of a Mucuna pruriens seed extract (MPE) and tested its in vivo efficacy against Echis carinatus venom (EV) in short- (1 injection) and long-term (three weekly injections) treatments. The aim of the present study was to investigate plasma proteome changes associated with MPE treatments and identify proteins responsible for survival of envenomated mice (CHALLENGED mice). Six treatment groups were studied. Three control groups: one saline, one short-term and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Proteomic analysis, for example, indicated that the MPE pre-treatment also elicited the activation of counterbalancing processes to compensate for the imbalances caused by Echis carinatus venom (Guerranti et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis, for example, indicated that the MPE pre-treatment also elicited the activation of counterbalancing processes to compensate for the imbalances caused by Echis carinatus venom (Guerranti et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Mucuna pruriens and its glycoprotein extract were prepared as previously described in Guerranti et al . (). Eluted fractions were assayed for protein concentration by the dye‐binding method of Bradford () and purity checked with sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS‐PAGE).…”
Section: Methodsmentioning
confidence: 97%
“…Mucuna pruriens has been studied extensively for its chemical, pharmacological (Iauk et al ., ; Katzenschlager et al ., ) and antisnake venom properties (Houghton and Osibogun, ; Ogueli et al ., ; Guerranti et al ., , ; Soares et al ., ). In a separate study by Machuka (), the total protein extract from M. pruriens seeds inhibited trypsin and chymotrypsin activities.…”
Section: Introductionmentioning
confidence: 97%
“…High-throughput proteomic/transcriptomic snake venom analyses have proved the presence of various SPases in the venoms of crotalidae and viperidae snakes (Calvete et al, 2007; Fox et al, 2006; Guerranti et al, 2008; Li et al, 2004; Serrano et al, 2005). …”
Section: Introductionmentioning
confidence: 99%